Analisis Putusan Mahkamah Agung tentang Uji Materiil Peraturan Presiden tentang Jaminan Kesehatan Pendekatan Teori Sistem Hukum - Ade Ramli; Akhmaddhian, Suwari (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2025)
This study aims to examine the legal basis and authority of the President in issuing the Presidential Regulation on Health Insurance, specifically regarding the BPJS Kesehatan contribution policy, which is deemed not fully in line with statutory provisions. The method used is normative juridical, with a legislative approach and a literature review of the National Social Security Law (SJSN), the BPJS Law, and the Presidential Regulation on the National Health Insurance (JKN). Data were analyzed qualitatively to assess the conformity of the Presidential Regulation's material with the hierarchy of norms and the limits of delegation of authority. The results indicate that several provisions in the Presidential Regulation, particularly regarding the contribution determination mechanism, lack a clear basis for delegation, thus creating normative conflicts and expanding executive authority beyond that granted by law. The Supreme Court's decision to annul the provision on contribution increases reinforces the importance of the principles of legality, legal certainty, and judicial oversight in the implementation of the JKN. In conclusion, the judicial review mechanism plays a crucial role in ensuring the Presidential Regulation remains consistent with the law, thus requiring more careful and transparent regulation development in the field of Health Insurance.